Projekt stanowiska eksperymentalnego do badania krzepnięcia w przestrzeni walcowej = The test stand project to analysis solidification in cylinder space - Gortych, Marta; Gortych, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents an experimental design to test the position of the solidification process around the cylindrical surface. Characterized the convection and solidification process around the horizontal cylinder and inclined. The distribution of the local heat transfer coefficient of the flow around a transverse horizontal cylinder. A combination solidification phenomena and convection of the liquid around the cylindrical surface.
Keywords: proces krzepnięcia; konwekcja swobodna; powierzania walcowa; solidification process; free convection; cylindrical space